How Linker’s Modification Controls Swelling Properties of Highly Flexible Iron(III) Dicarboxylates MIL-88 - Horcajada, Patricia; Salles, Fabrice; Wuttke, Stefan; Devic, Thomas; Heurtaux, Daniela; Maurin, Guillaume; Vimont, Alexandre; Daturi, Marco; David, Olivier; Magnier, Emmanuel; Stock, Norbert; Filinchuk, Yaroslav; et al. (Journal of the American Chemical Society, 2011)
A series of organically modified iron(III) terephthalate MIL-88B and iron(III) 4,4′-biphenyl dicarboxylate MIL-88D flexible solids have been synthesized and characterized through a combination of X-ray diffraction, IR spectroscopy, and thermal analysis (MIL stands for Material from Institut Lavoisier). The swelling amplitude of the highly flexible MOFs tuned by introducing functional groups onto the phenyl rings shows a clear dependence on the steric hindrance and on the number of groups per aromatic ring. For instance, while the introduction of four methyl groups per spacer in dried MIL-88B results in a large permanent porosity, introducing two or four methyl groups in MIL-88D allows an easier pore opening in the presence of liquids without drastically decreasing the swelling magnitude. The influence of the degree of saturation of the metal center and the nature of the solvent on the swelling is also discussed. Finally, a computationally assisted structure determination has led to a proposal of plausible structures for the closed (dried) and open forms of modified MIL-88B and MIL-88D and to evaluation of their framework energies subject to the nature of the functional groups.